A matemática contábil: das lides comerciais para os cursos secundários técnicos e sua transformação em setor acadêmico no Brasil (1808-1970) - Gouveia Neto, Sérgio Candido de [UNESP] (2015)
Commercial labors, to trade courses and more recently to higher education courses in Accounting, mathematical knowledge always figured. In this sense, he wonders how the book mathematical turned into school knowledge and gained subsequently status of academic knowledge in Brazil. To try to answer this question, the work outlined here has the general objective to analyze the route of the accounting math in commercial litigations, later appropriated by regular teaching (trade school, technical trade courses and higher education courses in Accounting). In theoretical and methodological tools we use to Geertz's definition of culture, school culture Julia, school discipline Chervel and Goodson curriculum. The sources used consisted of math textbooks (mathematics, financial mathematics, etc.), legislation, journals accounting area, historical articles and various other documents. In general, we show the beginnings of mathematics and accounting relations with mercantile culture. Later, we treat schooling of market knowledge for a professional technical school culture. Finally, it addressed the transition from school accounting math to the academic level